PENGARUH MODERASI INFORMASI ASIMETRI DAN GROUP COHESIVENESS TERHADAP HUBUNGAN PARTISIPASI PENGANGGARAN DENGAN BUDGETARY SLACK - Putranto, Yohannes Andri (Jurnal Economia, 2012)
Abstract: The Moderating Effects of Asymmetry Information and Group Cohesiveness on the Relationship between Budgetary Participation and Budgetary Slack. This study examines the moderating effects of asymmetry information and group cohesiveness on the relationship between budgetary participation and budgetary slack. Using the moderated regression analysis and base on a sample of 38 functional managers at branded car dealer and service. The results show no interaction between asymmetry information, group cohesiveness, and budgetary participation affecting budgetary slack. Keywords: asymmetry information, group cohesiveness, budgetary participation, budgetary slack. Abstrak: Pengaruh Moderasi Informasi Asimetri dan Group Cohesiveness terhadap Hubungan Partisipasi Penganggaran dengan Budgetary Slack. Penelitian ini menguji efek moderasi informasi asimetri dan kekohesifan kelompok terhadap hubungan antara partisipasi penganggaran dengan budgetary slack. Sampel penelitian ini adalah manager-manager fungsional perusahaan dealer dan servis mobil. Hasil uji statistik regresi moderasi menunjukkan bahwa asimetri informasi dan kekohesifan kelompok tidak terdukung sebagai variabel moderasi. Kata kunci: informasi asimetri, kekohesifan kelompok, partisipasi penganggaran, dan budgetary slack